Investigation of isolated lipase producing bacteria from oil-contaminated soil with proteomic analysis of its proteins responsive to lipase inducer - Khemika Lomthaisong (2018)
Forty bacterial strains isolated from oil-contaminated soil were screened for lipase production on selective medium using neutral red as an indicator. Nine lipase producing bacterial isolates indicated by the formation of red halo were found. The lipolytic activities produced by these bacteria were then compared. The highest enzyme activity of 163.51 U mL -1 was shown by the CFS14 isolate. Species identification of the CFS14 isolate was then performed by 16S rRNA gene sequencing. The DNA sequence showed the maximal similarity to Pseudomonas xinjiangensis with 99.6%. Lipase productions by P. xinjiangensis strain CFS14 were investigated in different cultured conditions. The bacteria produced the highest lipase activity when cultured in the medium of pH 8.0 supplemented with 0.5% MgCl 2, at 37 °C for 36 h. Proteins related to the lipase induction by 0.5% MgC1 2 were examined by proteomic analysis. The protein patterns of P. xinjiangensis CFS14 cultured in the medium supplemented with 0.5% MgCl 2, were compared with those of controls. Fifteen spots (6 increasing, 1 decreasing, 8 supplementary) from treated bacteria were different in protein abundance from controls. Five chosen protein spots were identified by MALDI-TOF mass spectrometry combined with bioinformatic methods. Only 2 protein spots could be identified which were likely to be lipoprotein and hypothetical protein cdivTM_18888. © 2012 Asian Network for Scientific Information.